Pengaruh Motivasi Belanja Hedonis terhadap Impulse Buying pada Generasi Z di Sleman - Ahmad Sufyan; Anggita Cahya Dewanti; Lara Lorenza (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to analyze the extent to which hedonic shopping motivation influences impulse buying behavior among Generation Z, particularly in Sleman Regency. Hedonic shopping motivation is viewed as a drive to shop fueled by emotions of pleasure and the desire to alleviate boredom or relieve feelings of anxiety. The research method employed is a survey with a quantitative approach, where data were collected through questionnaires distributed to 100 Generation Z respondents who shop in the Sleman area. The regression analysis results indicate that hedonic shopping motivation has a significant influence on impulse buying behavior, with a significance value of 0.000, which is smaller than 0.05, and a t-value of 11.252. This suggests that the higher the hedonic shopping motivation, the more likely the tendency to engage in impulse buying. Based on the research findings, it can be concluded that strategies involving awareness of the influence of hedonic shopping motivation are essential in helping Generation Z make wiser shopping decisions and better manage impulse buying behavior.